A Periodic Tracking MPC that is Locally Equivalent to Periodic Economic MPC*. Issue 1 (July 2017) - Zanon, Mario; Gros, Séebastien; Diehl, Moritz
Abstract: Stability for economic Model Predictive Control (MPC) is in general difficult to establish. In contrast, tracking MPC has well-established stability guarantees, but can yield poor closed-loop performance in terms of the selected economic criterion. In Zanon et al. (2016), a formal procedure to design a tracking MPC scheme so as to locally approximate the behaviour of economic MPC was proposed for the case of optimal steady-state operation. In this paper, we extend that result to the periodic case and provide a procedure to compute the tracking stage cost numerically. We illustrate our developments in a simulated example.